Determinação experimental de Coeficientes de Atrito de diferentes partículas para aplicação na modelagem de escoamentos densos - Andrade, Larissa Pacheco (Universidade Federal de São Carlos, 2022)
Systems involving particles are very common in many engineering applications. The interaction between these particles and of them with the equipment surfaces can strongly affect their dis-tribution, which will often influence the yield or efficiency of a process. Because of this, it is important to know how this interaction takes place. Friction coefficients are fundamental pa-rameters for studying the movement and interaction of particles, especially when their concen-tration is high. The direct determination of these coefficients is often a complex task, since their measurement can be affected by a number of factors, such as the flatness of the surface and the shape of the particle. Because of this, there are few works that make the direct exper-imental determination of these coefficients. Studies relating these parameters to the character-istics of particles and surfaces are even rarer. In this context, this work aimed to obtain exper-imentally the coefficients of static and dynamic friction of particles with different physical, elastic and surface properties, and to test different methodologies for their determination. Ac-rylonitrile Butadiene Styrene (ABS), fluorelastomer, nitrile rubber, alumina and porcelain par-ticles were used in these tests. Two methodologies were used to determine the rolling friction coefficient: ASTM G194-08 (2008) and the oblique throw method proposed by Goya et al. (2014) and Neto and Cruz (2015). For the sliding friction coefficient, two other methodolo-gies were used: the inclined plane method (Lima, 2017) and the method of determination from the analysis of data obtained by the inclined ramp method (Goya et al., 2014). Acrylic and glass surfaces were used to determine the friction coefficients for the particle-surface pairs. The results showed that there is an influence of surface and elastic properties on the co-efficients. Furthermore, it was possible to verify that the applied method can also have an in-fluence on the values of the coefficients. For rolling friction, for example, the different meth-ods resulted in similar values only for particles with more uniform surfaces, indicating that care is needed in choosing the method when working with particles with less uniform surfac-es. The present study was mainly useful in comparing direct methods for determining friction coefficients. However, further investigation of the influence of particle properties on these parameters is necessary, in order to enable the correlation of these variables.
Experimental determination of Friction Coefficients of different particles for application in the modeling of dense flows
Keywords: Coeficientes de atrito; Rolamento; Deslizamento; Rugosidade; Métodos; Friction coefficients; Rolling; Sliding; Roughness; Methods; ENGENHARIAS::ENGENHARIA MECANICA::ENGENHARIA TERMICA::CONTROLE AMBIENTAL